Crustal structure and magma plumbing system beneath the Puer Basin, southwest China: Insights from three-dimensional magnetotelluric imaging - Cheng, Yuanzhi; Tang, Ji; Chen, Xiaobin; Dong, Zeyi; Wang, Libo (Tectonophysics, 2019)
The Puer Basin region, where Yangtze continental block and the Tethyan orogen collide, provides a favorable area for studying the processes of magmatic evolution, intracontinental earthquakes and hydrothermal systems. Focused on these issues, we have acquired a three-dimensional electrical model of the Puer Basin in southern Yunnan, using broadband magnetotelluric data extending from 320 to 0.001 Hz along eight profiles covering the Puer Basin. The complex subsurface model is filled with zones of fluid-filled fracture, partial melt networks, regional faults, and cold plutons. There are two highly conductive zones (3–10 Ωm) beneath the Puer Basin from 10 km to 35 km in depth. The estimated melt fractions are in the range of 4–26 vol%, which is required to account for the observed high conductivities in the crust based on the formulation of the multiple conduction models and resistivity from the three-dimensional magnetotelluric inversion. The partial melt in the middle and lower crust may have been derived from either magma intrusion of the mantle sources or the dehydration processes in the slab subducting of Yangtze continental block beneath the Tethyan orogen in southern Yunnan. Based on the three-dimensional electrical model, integrating with crustal anisotropy, thermal structure, potential field and seismic survey results, we have a more comprehensive understanding of the mechanism of the hydrothermal system, seismotectonics, and deep seismogenic background. •We have obtained a three-dimensional electrical model of the Puer Basin in southern Yunnan.•3D electrical model reveals two magma chambers in mid-lower crust in the Puer Basin.•Seismicity and hydrothermal activity appears to be controlled by the conductive zones in mid-lower crust.